1999
DOI: 10.1007/s11664-999-0042-x
|View full text |Cite
|
Sign up to set email alerts
|

Junction depth measurement in HgCdTe using laser beam induced current (LBIC)

Abstract: A new, nondestructive junction depth measurement technique for HgCdTe photovoltaic devices is investigated. The technique uses a scanning laser microscope to obtain laser beam induced current (LBIC) data from which information regarding the junction depth is extracted, and is applicable to both homojunction and heterojunction diodes. For implanted heterojunction photodiodes, the position of the n-p junction relative to the heterojunction is an important factor determining completed device performance, with bli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…2(a). It can be found that the peak magnitude and shape of LBIC vary with the junction depth in good agreement with the reported experimental data [9]. The peak magnitude of LBIC monotonously increases with increasing junction depth, but the slope in the n-type region decreases.…”
Section: Resultssupporting
confidence: 90%
“…2(a). It can be found that the peak magnitude and shape of LBIC vary with the junction depth in good agreement with the reported experimental data [9]. The peak magnitude of LBIC monotonously increases with increasing junction depth, but the slope in the n-type region decreases.…”
Section: Resultssupporting
confidence: 90%
“…The CdTe was used both as a passivant and a mask for the plasma-based conversion [6,7] to form n-on-p junction. This process results in a junction depth [8] of approximately 3 lm and sideway spread of 1 lm. Following the junction formation, the devices were passivated with 200 nm thick ZnS film by thermal evaporation.…”
Section: Methodsmentioning
confidence: 99%
“…To convert a portion of the epilayer to n-type, the sample was exposed for 2 min to a methane/hydrogen plasma in a parallel-plate RIE system with ϳ100-W radio-frequency power, a total flow rate of ϳ40 sccm (5:1 H 2 /CH 4 ratio), and a total pressure of ϳ500 mtorr. The conversion depth of 2 Ϯ 0.5 µm was obtained from successive wet etching and laser-beam-induced current imaging, 18 performed on a piece of the same sample cut from the wafer. The Hall and resistivity measurements were performed in the van der Pauw configuration at magnetic fields varying from 0 T to 12 T. The Hall coefficient and resistivity were calculated for the combined n-on-p structure in the standard manner, with a Hall scattering coefficient equal to one.…”
Section: N-on-p Structurementioning
confidence: 99%
“…One expects the electron density to decrease with depth (similar in manner to p-to-n type conversion by mercury in-diffusion), while the electron mobility should increase with depth because of the lower donor density and improving crystal quality. To verify this hypothesis, the n-layer, known from other experiments to be about 2-µm thick, 18,19 was hypothetically divided into four 0.5-µm-thick layers. Assigning to each layer a concentration obtained from the mobility spectrum, with low mobility and high concentration at the first surface layer and maximum mobility with lowest concentration at the last, leads to the profile shown in Fig.…”
Section: N-on-p Structurementioning
confidence: 99%